INSTABILITY OF A12SIO5 "TRIPLE-POINT" ASSEMBLAGES IN MUSCOVITE+BIOTITE+QUARTZ-BEARING METAPELITES, WITH IMPLICATIONS - Pattison D.R.M. (My University, 2001)
This paper uses constraints from experiments, thermodynamic modeling, and natural mineral assemblages to argue that Al2SiO5 "triple-point" assemblages, in which all three Al2SiO5 minerals are in stable equilibrium, are not possible in common muscovite(Ms)+biotite(Bt)+quartz(Qtz)-bearing metapelitic rocks because the reactions that first introduce an Al2SiO5 mineral to these bulk compositions occur at higher temperature than the triple point. Less-common, highly aluminous bulk compositions may develop Al2SiO5 minerals at temperatures below the triple point such that stable triple-point assemblages are theoretically possible. The "invisibility" of the triple-point to common Ms+Bt+Qtz-bearing metapelites calls into question most metapelitic triple-point localities reported in the literature, and carries implications for the topology of the metapelitic petrogenetic grid, the bathozone/bathograd scheme of Carmichael (1978), and the possibility of prograde kyanite → andalusite → sillimanite sequences. Re-examination of reported triple-point localities suggests that in most if not all cases, the Al2SiO5 minerals grew at different times in the metamorphic history of the rock.